Contribution of Hemoglobin Levels and Lung Capacity to Maximum Oxygen Uptake Ability - Lawanis, Haripah; Setiawan, Yogi; Syampurma, Hilmainur; Mardius, Ali; Astuti, Yuni (Indonesian Journal of Sport Management, 2024)
The problem in this study is based on field observations; the ability of West Sumatra Hockey athletes to take oxygen could be much higher. Internal factors and external factors of the athlete influence this. One of these internal factors is the physical condition related to the ability to take oxygen optimally. This study aims to determine the contribution of hemoglobin levels and vital lung capacity to the maximum oxygen uptake ability (VO2 max) of West Sumatran Hockey athletes. This research method is a quantitative method using a correlational research design. The population in this study is West Sumatran Hockey. In contrast, the sample in this study was taken using a total sampling technique, namely West Sumatran Hockey, who will participate in the 20222 National Championship, totaling 24 people. The instrument for collecting data for hemoglobin levels was a spectrophotometer and a rotary spirometer for vital lung capacity, while for VO2 max, an intermittent recovery test was used. The data was analyzed using correlation analysis techniques, simple regression, correlation, and multiple regression. The results of data analysis showed that: (1) Hemoglobin contributed to the VO2 max ability of West Sumatra Hockey by 21.73%. (2) Lung vital capacity contributes to West Sumatra's VO2 max Hockey ability by 16.46%. And (4) Hemoglobin and vital lung capacity jointly contribute to the ability of VO2 max by 25%.